Analisis Histologis Ginjal Ikan Asang (Osteochilus hasseltii ) di Danau Maninjau dan Singkarak, Sumatera Barat - Sayati Mandia; Netti Marusin; Putra Santoso (Jurnal Biologi Universitas Andalas, 2013)
A study on kidney histology of Silver Sharkminnow (Osteochilus hassletii) sampled from Maninjau and Singkarak Lakes, West Sumatra has been done from December 2012 to April 2013 at Animal Structure and Development Laboratory, Department of Biology, Andalas University, Padang. Direct observation and purposive sampling were conducted at four locations around Singkarak Lake (Sumani, Paninggahan, Sumpur, Ombilin) and one location in Maninjau Lake (Tanjung Sani). Histological samples of kidneys were isolated, fixated, dehydrated and embedded on paraffin and stained using Haematoxylin-Eosin. The results showed some histological alterations of kidney samples from all locations. Those alteration varied from cell hypertrophy, lysis, necrosis and emerging of scrape tissues. There were no significant differences on the degree of alteration among all populations. Those result indicated that both lakes had been experienced organic pollutions.Keywords: Silver Sharkminnow (Osteochilus hasseltii C.V), Histopatology, Kidney, Singkarak Lake, Maninjau Lake.